2021
DOI: 10.25259/kpj_34_2020
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin responsive conditions in pediatric neurology

Abstract: Vitamin responsive conditions can be either due to inherited defects in the metabolic pathways resulting in vitamin dependency or due to acquired deficiency states. Due to widespread malnutrition and predominantly vegetarian population in India, vitamin deficiency state is quite common and early identification is essential. Inherited defects, if treated earlier, lead to reduced morbidity and mortality and improvement in long-term neurocognitive outcomes. Various vitamin responsive conditions in pediatric neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Moreover, the researchers 54 noted that there was a slowing down in hepatic tumor induction by azo-dyes in rats fed with both riboflavin and cupric oxyacetate hexahydrate. Furthermore, the authors 55 observed the neuroprotective effects of riboflavin in mitochondrial dysfunction disorders and several neurological conditions such as neuroinflammation and glutamate excitotoxicity 56 . Moreover, riboflavin deficiency led to an increase in homocysteine or kynurenines levels which in turn caused marked neurological consequences because a vital role was played by riboflavin and the active form of pyridoxine in the metabolism of homocysteine and the pathway of tryptophan kynurenine 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the researchers 54 noted that there was a slowing down in hepatic tumor induction by azo-dyes in rats fed with both riboflavin and cupric oxyacetate hexahydrate. Furthermore, the authors 55 observed the neuroprotective effects of riboflavin in mitochondrial dysfunction disorders and several neurological conditions such as neuroinflammation and glutamate excitotoxicity 56 . Moreover, riboflavin deficiency led to an increase in homocysteine or kynurenines levels which in turn caused marked neurological consequences because a vital role was played by riboflavin and the active form of pyridoxine in the metabolism of homocysteine and the pathway of tryptophan kynurenine 55 .…”
Section: Discussionmentioning
confidence: 99%